FEASIBILITY STUDY OF INFORMATION SYSTEMS IN PLANTATION APB - Dwi Setyowati; Rafael Abdul Gafar, Ir Rafael Abdul Gafar, Ir (Jurnal Sistem Informasi, 1997)
On today's progress in the field of information technology in a very positive impact insupporting the smooth flow of information that is needed by every human being onearth. information needs of a computer system is something important in supportingthe operational activities of companies in which the computer information system ishighly efficient and effective in its use. with rapid advances in technology today,hence to reduce the barriers that arise due to the large volume and limited personnelin APB plantations, the author tries to do a feasibility study by conductinginformation systems analysis and discussion in three aspects: technical, operationaland economic .As for the reasons dealt with the three aspects mentioned above, since all three ofthese aspects more important role in the development of computer-based informationsystem while the legal aspects and the schedule was not discussed because it wasquite clear about the legality and in terms of the schedule is not binding.Of the results of research and discussion of these three aspects, namely technical,operational and economic aspects we concluded that all three aspects are quitereasonable and supports the existence of computer-based information systems in APBplantations, in order to support administrative and operational activities.